자외선 파장을 활용한 항균 화장품 케이스 개발 - 염승훈(Seung Hoon Yum); 정인근(In Geung Jung); 정재영(Jae Young Jeong); 황유진(You Jin Hwang) (한국컴퓨터정보학회논문지, 2020)
본 연구에서는 자외선 파장을 활용한 항균 화장품 케이스를 개발하고자 하였다. UVC는 경제성및 편리성 면에서 우수한 항균 성능을 가진다. 실험은 이를 입증하고 적합한 투과 재질을 찾는것을 목적으로 진행하였다. 실험에는 자외선 파장을 이용한 항균 화장품 케이스의 항균력을 측정· 비교하기 위해 UVA, UVC 기기 및 타사 제품을 사용하였다. 실험 대상 균주로는 그람양성균인 S. aureus를 사용하였으며, 항균력은 평판계수법을 통해 대상 균주의 집락 수를 측정·비교하였다. 실험 결과는 UVA와 UVC 모두 항균 활성을 나타냈고, UVC가 가장 뛰어난 항균 활성을 나타냈다. 결론적으로 UVC를 직접투과 할 때 석영유리가 가장 적합하지만 검사한 재질의 두께가 두꺼워질수록 항균력이 감소하였다. In this study, we propose an antibacterial cosmetic case using UV wavelengths. UVC have excellent antibacterial strength in terms of economics and convenience. The purpose of experiments was to prove it and to select a suitable permeability material. In experiments, UVA, UVC machanics and the competitor product were used to measure and compare the antibacterial strength of antibacterial cosmetic case using UV wavelength. S. aureus, a gram-positive strain, was used subject to the experiment, and the antibacterial strength measured and compared the number of colonies using the plate count technique. As a result, both UVA　and UVC showed antibacterial activity, and UVC showed the most powerful antibacterial activity. In Conclusion, the Quartz glass was the most suitable of the permeable materials, but the more thick the examined quartz material became the less antibacterial strength. KCI Citation Count: 0